2017
DOI: 10.14202/vetworld.2017.1347-1352
|View full text |Cite
|
Sign up to set email alerts
|

Reducing zoonotic and internal parasite burdens in pigs using a pig confinement system

Abstract: Aim:This study was designed to validate the effectiveness of the pig confinement system (PCS) in reducing the prevalence of zoonotic and internal parasite burdens in pigs.Materials and Methods:Ten PCS households were selected together with 10 households practising traditional scavenging systems. Five pigs were monitored per household every 3 months for 15 months and blood and feces collected. Pigs received a single dose of oxfendazole at 30 mg/kg at baseline. Qualitative fecal examinations for intestinal paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
3
15
0
2
Order By: Relevance
“…Other common zoonotic parasites include Taenia solium , Trichinella spiralis , Toxoplasma gondii , and Sarcocystis suihominis [ 11 , 17 ]. A study conducted in southern part of Rwanda found that larvae of Taenia solium ( Cysticercus cellulosae ) caused 23.3% of epileptic cases in people [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other common zoonotic parasites include Taenia solium , Trichinella spiralis , Toxoplasma gondii , and Sarcocystis suihominis [ 11 , 17 ]. A study conducted in southern part of Rwanda found that larvae of Taenia solium ( Cysticercus cellulosae ) caused 23.3% of epileptic cases in people [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is more likely that coinfections found in this study would considerably contribute to the reduction of the production and performance of the pigs [ 10 ]. Although pig farmers may not be aware due to subclinical infections, economic losses caused by endoparasites are important [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it favours the spread of diseases through direct contact while mixing with other herds or wild boar [ 16 , 21 23 ], or by scavenging on infected food, carcasses or other fomites [ 24 ]. Moreover, confining pigs has been shown to lead to lower prevalence of diseases like zoonoses and internal parasites [ 25 ]. However, these systems are difficult to change, since they go deep into the traditions and roots of the communities and allow the production of pigs with minimum investments (in terms of feeding, fencing or personnel).…”
Section: Discussionmentioning
confidence: 99%
“…Faktor management pemeliharaan merupakan faktor yang paling dominan mempengaruhi kejadian infeksi parasit. Dengan kondisi seperti ini penanggulangan penyakit parasit tidak menjadi perhatian peternak sehingga dapat menghambat produktivitas ternak sapi yang disebabkan adanya penyakit parasit seperti cacingan atau infeksi protozoa (Agustina et al, 2016;Agustina et al, 2017).…”
Section: Pendahuluanunclassified